Peran Peran Konseling Individual Dengan Metode Mindfulness Dalam memgatasi Kecemasan Pada Remaja Di LPKA Kelas I Palembang - Poppy Ulandari; Abdur Razzaq; Lena Marianti (Journal of Society Counseling, 2023)
Anxiety is a normal thing that can happen to every individual, but anxiety can be said to be deviant if the individual is unable to reduce the anxiety in situations where most people are able to handle it without any significant difficulties. This research is entitled "The Role of Individual Counseling Using the Mindfulness Method in Overcoming Anxiety in Adolescents at Class I LPKA Palembang". The results of this study were that before individual counseling was given, it was seen that adolescents were not aware of the anxiety disorders they sometimes experienced, which was shown by behaviors such as irritability, irritability, difficulty concentrating, and fear of what would happen. This individual counseling was carried out in 4 meetings and with 3 individual counseling stages. With techniques that teenagers can apply in everyday life such as deep breathing, self-talk, and visual/guided imagery techniques so that anxiety disorders in adolescents can be resolved in terms of adolescents who are starting to calm down and are able to manage their emotions so they can avoid anxiety disorders.